DESCRIPTION AND DIFFERENCE OF SOCIAL CAPITAL IN AN INTERCULTURAL CONTEXT. THE CASE OF NURSING STUDENTS - Marco Alberto Núñez-Ramírez; Rosario del Carmen Realpozo-Reyes; Gloria Esthela González-Quirarte (Ra Ximhai, 2015)
The aim of this research is to assess the social capital of intercultural nursing students. We made a quantitative, exploratory and transverse study with a non-experimental design. A sample was taken composed of 55 intercultural nursing students of the Intercultural University of the State of Tabasco at Oxolotán, during the months of November and December 2014. A questionnaire for measuring social capital for indigenous peoples was administered. We found high levels of social capital; however, there were not significant differences according the State of provenance and the pertinence to a native group using student’s t distribution. Also we noted the need for the mediator intervention of the University to employ social capital as a strategic element to promote community development and ensure an inclusive access to public health through empowered nursing professionals who are subject of action for common good.